Sharing Economy and Sustainability Logic: Analyzing the Use of Shared Bikes - Suzenny T. Rechene (BAR: Brazilian Administration Review, 2018)
A sustainability-oriented logic is required in order to change the consumerist logic of the society. This is possible by changing the beliefs and values shared among stakeholders regarding their behaviors. The institutional logic of sustainability (ILS) concept emerges in response to this need. In the context of the sharing economy, this research aims to understand the formation of ILS with the implementation of shared bikes in the city of Fortaleza-CE. Therefore, an in-depth case study was developed with actors that developed the Bicicletar project. The results demonstrate that: (a) several events happened to enable the insertion of the project; (b) city hall played a prominent role as a stimulator of change; (c) the city's mobility structure has been modified; and (d) sustainability practices are observed in all dimensions, with an emphasis on the environmental one. With this discussion, we contribute to the understanding of how sustainability can be practiced in other contexts. There is also the contribution of theoretical elements that facilitate understanding of the sustainability concept.